Pengaruh variasi komposisi serat tandan kosong sawit (TKS) dan serbuk kayu terhadap sifat fisis dan sifat mekanis papan partikel (The effect of variations in the composition of the fiber composition of the empty palm fruit bunches and sawdust on physical and mechanical properties of particleboard) - Fadillah Ulfah; - Syakbaniah; Yenni Darvina (Department of Physics – Universitas Negeri Padang UNP, 2015)
This study aims to determine the effect variations composition of Palm Empty Fruit Bunch (EFB) and wood dust on the physical properties and mechanical properties of particle board. Particle board is made from EFB fiber and wood dust and added 30% adhesive. each particle boards have various compositions. In this study, the independent variable in the form of variations in the composition of the EFB fiber and wood dust that is 20: 80%, 40: 60%, 50: 50%, 60: 40%, 80%: 20%. The dependent variable in the form of physical properties such as moisture content, density, and mechanical properties such as flexural strength and compressive strength.. In general the values obtained physical and mechanical propertiesare density, flexural strength, compressive strength which is optimal in the variation 50% EFB : 50% wood dust, but the moisture content obtained optimal value at variation 40% EFB: 60% wood dust. All fulfill the SNI standard except for the value of the flexural strength